Te devo uma carta sobre o Brasil e este sonho: Entrevista com Carol Benjamin - França Martins, Andréa; Machado, Patrícia; Cunegundes Guimarães, Patrícia (Imagofagia, 2022)
Entrevista com Carol Benjamin.